Аналіз поширення радіосигналів міліметрового діапазону через дощі у мережах зв'язку 5 G - Водолажченко, О. В. (ХНУРЕ, 2022)
The range of millimeter waves is not yet very actively used and has not yet been fully studied. Therefore, it is of interest to study the capabilities of 5G mobile communications in this wavelength range. The analysis of signal attenuation in free space from precipitation intensity at different values of optical visibility at the frequency of 30 GHz and at the frequency of 60 GHz is carried out. The analysis showed that the intensity of precipitation and optical visibility affect the attenuation of the signal, and is about 4 dB loss at 30 GHz and about 12 dB loss at 60 GHz.